2019
DOI: 10.1073/pnas.1909816116
|View full text |Cite
|
Sign up to set email alerts
|

Rapid increase in Asian bottles in the South Atlantic Ocean indicates major debris inputs from ships

Abstract: Most plastic debris floating at sea is thought to come from land-based sources, but there is little direct evidence to support this assumption. Since 1984, stranded debris has been recorded along the west coast of Inaccessible Island, a remote, uninhabited island in the central South Atlantic Ocean that has a very high macrodebris load (∼5 kg·m−1). Plastic drink bottles show the fastest growth rate, increasing at 15% per year compared with 7% per year for other debris types. In 2018, we examined 2,580 plastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(58 citation statements)
references
References 33 publications
8
50
0
Order By: Relevance
“…This higher connectivity with the continent contrasts with the low proportion of recognizable continental litter items stranding on Easter Island 26,30 , which suggests that continental plastic litter either does not reach the EIE or does so in an already degraded state. Similar results were recently reported for the oceanic Inaccessible Island in the South Atlantic, where most recognizable litter also seems to have oceanic sources originating from shipping and fisheries 60 .…”
Section: Discussionsupporting
confidence: 89%
“…This higher connectivity with the continent contrasts with the low proportion of recognizable continental litter items stranding on Easter Island 26,30 , which suggests that continental plastic litter either does not reach the EIE or does so in an already degraded state. Similar results were recently reported for the oceanic Inaccessible Island in the South Atlantic, where most recognizable litter also seems to have oceanic sources originating from shipping and fisheries 60 .…”
Section: Discussionsupporting
confidence: 89%
“…Perhaps unsurprisingly, given its size and population density, 47% of plastic bottles found on Aldabra with intact labels were from China. This is similar to findings from islands in the Southern Atlantic Ocean 42 , and on Alphonse Island in Seychelles, where more than 75% of labelled items originated in Southeast Asia (mainly Indonesia and Thailand) and 13% originated in East Asia (mainly China) 29 . In both cases, the original studies suggested that the intact labels might indicate the source of the bottles was dumping from ships.…”
Section: Discussionsupporting
confidence: 89%
“…If the global model estimate is correct, we'd expect to see an annual stranding rate of 30-90 kg•m −1 , 20-60 times more than the total standing stock of plastic on the study beach. However, almost half of the mass of litter at the study beach comes from fishing and other marine activities, and some of the general rubbish is also dumped illegally from ships (Ryan et al, 2019). Even at heavily polluted urban beaches in Cape Town, extrapolated daily litter accumulation rates are only 0.4-16 kg•m −1…”
Section: Litter Typementioning
confidence: 98%